Prevalence and antimicrobial resistance profile of bacterial foodborne pathogens in Nile tilapia fish (Oreochromis niloticus) at points of retail sale in Nairobi, Kenya - Mumbo, Millicent T.; Nyaboga, Evans N.; Kinyua, Johnson; Muge, Edward K.; Mathenge, Scholastica G. K.; Muriira, Geoffrey; Rotich, Henry; Njiraini, Bernard; Njiru, Joshua M. (Frontiers in Antibiotics, 2023)
The aim of this study was to assess the prevalence, antimicrobial resistance patterns, antibiotic resistance genes and genetic diversity of bacterial food-borne pathogens recovered from fresh Nile tilapia obtained from retail markets in Nairobi, Kenya. A total of 68 Nile tilapia fish were randomly sampled from retail markets and tested for the presence of with Proteus, Staphylococcus aureus, Pseudomonas aeruginosa, Vibrio cholerae, and Vibrio parahemolyticus. Standard culture-based microbiological and Kirby-Bauer agar disk diffusion methods were used to isolate and determine the antimicrobial resistance patterns of the isolates to 11 selected antibiotics. The genetic diversity of the multidrug resistant (MDR) bacteria was determined using16S rRNA sequencing and phylogenetic analysis and polymerase chain reaction (PCR) was used for detection antibiotic resistant genes in MDR bacteria isolates. High levels of bacterial contamination was detected in fresh Nile tilapia fish (44/68, 64.71%). The prevalence of the presumptive bacteria identified was 44.12%, 10.29%, 4.41%, 2.94% and 2.94% for Proteus spp., Staphylococcus aureus, Pseudomonas aeruginosa, Vibrio cholerae and Vibrio parahemolyticus, respectively. Antimicrobial resistance was detected in all the bacteria species and all the isolates were resistant to at least one antibiotic except cefepime (30 µg). Additionally, 86.36% of the isolates exhibited multidrug resistance (MDR) with higher multiple antibiotic resistance indices (MAR index >0.3) indicating that fresh Nile tilapia fish was highly contaminated with MDR bacteria. Results of 16S rRNA sequences, BLASTn analysis and phylogenetic trees confirmed the identified MDR bacteria isolates as Proteus mirabilis and other Proteus spp., Staphylococcus aureus, Pseudomonas aeruginosa, Vibrio cholerae and Vibrio parahemolyticus. PCR analysis confirmed the presence of multiple antibiotic-resistance genes belonging to β-lactamases, tetracycline, sulfonamide, trimethoprim and aminoglycosides in all the MDR bacteria isolates. This study showed high prevalence of multidrug resistance among food-borne bacteria isolates from fresh Nile tilapia fish obtained from retail markets. From this study, we conclude that fresh Nile tilapia fish are a potential source of MDR bacteria, which could be a major risk to public health as a consequence of their dissemination along the human food chain.